A new classification for Freiberg's disease. (May 2022) - Hoggett, Lee; Nanavati, Nikhil; Cowden, James; Chadwick, Carolyn; Blundell, Chris; Davies, Howard; Davies, Mark B.
Highlights: Freiberg's osteochondrosis is an uncommon presentation with a variety of surgical management strategies employed after failure of conservative treatment. Established classification systems are not used to guide surgical management and no classification system us currently is used by surgeons to guide surgical treatment. The use of thin slice CT to evaluate the 'zone' of the defect may allow surgeons to pre-operatively determine the use of a rotational osteotomy using a simple classification system. Use of a classification system that guides treatment preoperatively aims to assist both surgical planning and patient consenting and counselling. Abstract: Introduction: Freiberg's osteochondrosis is an uncommon cause of foot pain. Following a national survey circulated by the British Foot and Ankle Society it was found that no classification is used to guide surgical treatment. This study aimed to create a simple, reproducible CT based classification to preoperatively plan whether an osteotomy is required. Methods: A retrospective review of 24 CT scans of new Freiberg's diseasediagnoses over a 10 year period was conducted. These images were assigned a study number and anonymised. The scans were then reviewed in their entirety by three independent specialists who determined whether an osteotomy would be of benefit. The sagittal CT slice that displayed the widest portion of proximal articular margin of the proximal phalanx was identified and divided the articular surface into 2 zones - plantar and dorsal and this formed the basis for our classification. These sagittal slices were then reviewed independently by two surgeons to determine if patients had disease in one or both zones and re-reviewed two weeks later to assess intra-observer reliability. Results: All 24 cases involved the second metatarsal. From reviewing the sagittal CT slices, it was felt that 18 patients were suitable for osteotomy and 6 were suitable for debridement +/− arthroplasty alone. The current classification demonstrated that 18 patients had disease confined to zone 1 only and the remaining patients had disease in both zones. Inter-observer reliability assessment had 95.8% agreement (Krippendorff's Alpha 0.897). Intra-observer reliability was 100%. Correlation of those observed to have isolated zone 1 disease and suitability for osteotomy was absolute (Pearson r = 1). Conclusion: Dividing the metatarsal head into two zones on the widest sagittal slice of the CT scan offers an easy reproducible way to preoperatively plan surgical treatment for Freiberg's osteochondrosis. Patients with isolated zone 1 disease should be suitable for an osteotomy.